P348 Perception of cancer risk in inflammatory bowel disease-associated dysplasia and management practice is influenced by colonoscopy experience and workplace affiliation: results of an international clinician survey. (27th May 2021) - Kabir, M; Thomas-Gibson, S; Hart, A; Wilson, A
Abstract: Background: A successful inflammatory bowel disease (IBD) surveillance cancer preventative programme requires effective action to be taken when dysplasia is detected. This is the first international cross-sectional study to evaluate current clinician understanding of IBD dysplasia risk, their management practice and adherence to the most recent international guidelines introduced since 2015. Methods: A 15-item online survey was disseminated to IBD gastroenterologist and colorectal surgeon members of the British Society of Gastroenterology in June 2019 and the European Crohn's and Colitis Organisation in February 2020. Results: 294 clinicians (93.5% gastroenterologists) from 60 countries responded. A significant proportion indicated not having access to high definition chromoendoscopy IBD surveillance (23%) in their endoscopy units. University hospitals were more likely than non-academic workplaces to provide second expert histopathologist review (67% vs. 46%; p=0.002) and formal multidisciplinary team meeting discussion (73% vs. 52%; p=0.001) of dysplasia cases. Most respondents would advocate endoscopic resection of all visible dysplasia and would refer to a regional specialist therapeutic endoscopist if needed (70%). However, perceptions of 5-year cancer risk associated with endoscopically unresectable low-grade dysplasia (LGD) varied between 0 – 100% (median 20% for visible LGD and median 25% for invisible LGD). Although most (98.4%) would advise a colectomy for endoscopically unresectable visible high-grade dysplasia (HGD), only 34.4% would also advise a colectomy for unresectable visible LGD. Working at a non-academic hospital was predictive of a lower perceived cancer risk with HGD [OR 0.4 (95% CI 0.23-0.95)] and unresectable LGD. Working in a private clinic predicted surveillance preference over colectomy to manage invisible LGD [OR 9.4 (95% CI 1.19-74.1)] and multifocal LGD. Greater surveillance colonoscopy experience predicted a lower preference for continued surveillance over colectomy for invisible LGD [OR 0.41 (95% CI 0.20-0.84)]. Conclusion: This study of mainly European gastroenterologists with a sub-specialist interest in IBD has revealed wide variations in colorectal cancer risk perceptions and dysplasia management practices. Clinicians with less IBD surveillance colonoscopy experience and from non-academic centres appeared to have lower cancer risk perceptions and were less likely to advocate colectomy over continued surveillance for high-risk LGD. This study suggests that further education is required to align current management practice with clinical guidelines.